The Study of Septic Tank Proximity on Coliform, E. Coli, and Organic Contamination in Shallow Groundwater: a Case Study of DKI Jakarta - Syifa Nadiyah Khairunnisa , Salsabila; Yanidar, Ramadhani; Megagupita Putri Marendra , Sheilla; Dwi Astuti, Ariani; Muhamad Taki, Herika (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
Groundwater in DKI Jakarta is subject to microbiological contamination. Approximately 32% of the population in DKI Jakarta relies on groundwater as an alternative source of clean water, highlighting the urgent need to address and prevent contamination. This study aims to investigate the effect of the separation distance between septic tanks and wells on the levels of Total coliform (TC), Escherichia coli (EC), and organic parameter contamination in shallow groundwater. Groundwater quality data, including TC, EC, and organic parameters from 265 monitoring points in DKI Jakarta, was obtained from the Jakarta Environment Agency in 2022. A quantitative descriptive approach, incorporating spatial mapping of bacterial and organic contamination using Geographic Information System (GIS) tools, was employed. MANOVA analysis using SPSS 26 was conducted to determine the relationship between septic tank distances and shallow water contamination levels. Results indicate that the separation distance between septic tanks and wells significantly influences TC and EC contamination in Jakarta Pusat, Jakarta Timur, and Jakarta Barat. Organic contamination, however, is significantly affected only in Jakarta Pusat and Jakarta Timur. In contrast, Jakarta Utara was identified as the most contaminated region, with 84% of groundwater samples showing TC contamination, 55% exhibiting Escherichia coli (EC) contamination, and 69% affected by organic pollution. However, these contaminations were not proven to be influenced by the proximity of septic tanks. This is likely due to the area's coastal location, where hydrogeological conditions and diverse pollution sources play a more significant role in groundwater contamination. Improvements in sanitation infrastructure could significantly enhance groundwater quality, particularly in highly vulnerable areas such as Jakarta Utara.